2015
DOI: 10.2174/1874331501509010030
|View full text |Cite
|
Sign up to set email alerts
|

Projection of Soil Organic Carbon Reserves in the Argentine Rolling Pampa Under Different Agronomic Scenarios. Relationship of these Reserves with Some Soil Properties

Abstract: Abstract:The soil organic carbon (SOC) of the Argiudolls of the Argentine Rolling Pampa evolves rapidly. Currently, the soils richest in SOC are cultivated with intensified crop sequences (e.g. maize-double cropped wheat/soybean, MWS) under no tillage (NT) and the poorest ones with soybean monoculture (S) under NT. There are great uncertainties about the future projections of SOC reserves and soil fertility associated with changes in land use and management. The aim of this study was to predict soil fertility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…These SOC data were published by Irizar et al. (2015) for NT and CP. In the case of MP, the data were not published.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…These SOC data were published by Irizar et al. (2015) for NT and CP. In the case of MP, the data were not published.…”
Section: Methodsmentioning
confidence: 90%
“…At the surface layer (A horizon), previous studies have reported that the distribution of TP in all analysed crop sequences responded to the long‐term effects of the tillage systems on SOC (Andriulo & Milesi, 2014). Additionally, it responded to the distribution of crop residues in the profile (Franzluebbers, 2004; Irizar et al., 2015). Below the A horizon, the observed TP increase towards the centre of the Bt1 horizon (40–50 cm) (Figure 1) results from the increased clay percentage (Arzuaga et al., 2005; Hernández et al., 1995; O'Halloran, 1993) and to the P enrichment of the OM with increasing depth (Alvarez et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability index was calculated as the ratio between the dry weight of over-0.5-mm aggregates and the dry weight of 1-2-mm aggregates and expressed as a percentage (Kemper 1965). Aggregate stability was classified as unstable (<20%), moderately stable (20-40%), and stable (>40%) (Irizar et al 2015). Soil organic carbon was determined by wet digestion by Walkley-Black method (Nelson and Sommers 1982), SON was determined by Kjeldahl method (Mulvaney 1996), and POC by the method of Cambardella and Elliot (1992), replacing chemical dispersion in the original method by mechanical dispersion through water agitation of the soil sample with glass balls during 5 h at 40 rpm (Irizar et al 2010).…”
Section: Plant and Soil Measurementsmentioning
confidence: 99%